Pelatihan Kecerdasan Emosional terhadap Self-Efficacy Mahasiswa Praktik Klinik Keperawatan Gawat Darurat - Ode Irman; Anggia Riske Wijayanti; Yohanes Paulus Pati Rangga (Jurnal Health Sains, 2021)
Self-efficacy becomes one of the important elements in the process of nursing education of the emergency department, because the situation in the emergency department with high workload, stress and anxiety can lead to not achieved in learning outcome. Interventions that can improve self-efficacy are training emotional intelligence. The purpose of the study was to explain the effect of emotional intelligence training on self-efficacy of students practicing emergency nursing clinics. Type of quasi experimental research with nonequivalent control group design design. A large sample of 42 people were taken with total sampling and divided into experimental and control groups, each group numbering 21 people. Emotional intelligence training is provided in 5 sessions (each session is 100 minutes). Self-efficacy is measured using General Self efficacy Scala (GSES). The research was conducted in April 2021 at the Nusa Nipa University. Data analysis using paired t test and independent t-test test. The results of the study showed there is an influence of emotional intelligence training on student self-efficacy (p 0.000). Before being given emotional intelligence training in the treatment group there was no difference in self-efficacy in the two groups (p 0.872), but after being given the training there was a difference of self-efficacy in the two groups (p 0.000). Emotional intelligence training can improve students' self-efficacy, it is expected that emotional intelligence and self-efficacy are considered and applied in the nursing curriculum.